(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The research aims to demonstrate the most important effective auditing procedures in accordance with the International Standard (710) for auditing, which defines the responsibility of the independent external auditor when auditing the current financial statements and matching them with the basic financial information included in the financial reports for the previous period in order to strengthen his opinion about the financial statements in general, as well as highlighting Light on the most important control observations issued by Iraqi Federal Financial Supervision Bureau resulting from auditing the comparative financial information of the current and previous government final account by matching the amounts in the financial records of some government institutions, which showed the presence of debit and credit account balances, advances and trusts that are contrary to their accounting nature, because the financial expenditures exceed the financial financing The receipt from the Ministry of Finance, based on the rights of others with these government institutions, despite the fact that the Iraqi Federal Financial Supervision Bureau held several meetings between institutions whose records show debit balances, advances, and trusts that are contrary to their nature.